Forced convection boundary layer slip flow over a plate in darcy-forchheimer porous medium - Abu Bakar, Shahirah (2014)
The boundary layer flows play a central role in many aspects of fluid dynamics since they describe the motion of a viscous fluid close to the surface. The forced convection can be enhanced passively by changing flow geometry, boundary conditions or by enhancing thermal conductivity of the fluid. A mathematical modeling of forced convection boundary layer flow over a plate in Darcy-Forchheimer porous medium is performed in this thesis. The aim of this thesis is to analyze the effects of velocity and thermal slips, chemical reaction with MHD (magnetohydrodynamics) and stagnation-point flow over shrinking sheet. The governing partial differential equations are transformed into ordinary differential equations by similarity transformation, which is then solved numerically using shooting method in MAPLE 15 software. The characteristics of the flow and heat transfer features for various of parameters are discussed and analyzed in detail. We found that the heat transfer increases with increasing permeability and velocity slip parameters but it decreases with increasing thermal slip parameter whereas the skin friction decreases with increasing velocity slip. Our analysis also reveals that the increase of the velocity slip parameter reduces the momentum boundary layer thickness and also enhances the heat transfer from the plate.